Notion in Motion: Teachers' Digital Competence - Monica Johannesen; Leikny Øgrim; Tonje Hilde Giæver (Universitetsforlaget, 2014)
Abstract The aim of this article is to shed critical light on the prevailing understanding of digital competence in schools and teacher education. There seems to be an emphasis on how to practice teaching with ICT throughout the Norwegian educational system. This article discusses and elaborates on the current approach, and argues for understanding digital competence from a broader perspective, by suggesting a framework for the notion of digital competence for teachers. This approach stresses teaching of, about, and with ICT.